Analisis Implementasi Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan PT Unilever Indonesia Tbk. - Athabarani, Imazizah; Febriyanti, Nor Maulidiya; Marina, Anna (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
The purpose of this study is to determine how PT Unilever Indonesia Tbk's financial statement quality is affected by the internal control system's implementation, which is based on the COSO framework. To guarantee the accuracy of financial data and stop fraud or mistakes in reporting, a strong internal control system is essential. This study was carried out utilizing the literature study method and a qualitative methodology. The findings demonstrated that PT Unilever Indonesia Tbk has fully implemented the five components of COSO internal control: information and communication, control operations, risk assessment, monitoring, and the control environment. The company's financial statements are of higher quality as a result of this deployment, according to all fair audit views. This study demonstrates that the secret to producing transparent and reliable financial accounts is methodical and consistent internal control. Keywords: Implementation of COSO-Based Control System; Five Components of COSO; Quality of Company Financial Statements